(untitled) (Fiep Bulletin - online, 2014)
The present article presents a proposal metodológica of education and learning centered in the development of the language human being - the orality, the reading and the writing. To say the world is the moment where the pupil develops its orality. The exchange of information and the dialógica inquiry are gifts. For the pupil it is the moment to display its knowledge, experiences and feelings in relation to one determined subject and to become related with the other; for the professor, when participating of this activity, it will have the chance to know the experiences of its pupils. To read the world means to report me it the idea of Pablo Freire (1986) on world reading that precedes the reading of the words. The pupil will go to know, to flood itself of knowing existing e (to re)construir it its context in accordance with. Here the educator will have to present the most different readings (of the body and other possibilities) that they assist in the production of knowing. To register the world synthecizes and registers this way covered. Professor and pupils can appeal to the most varied forms of register (artistic, reports, paper, pôsteres, periodical, daily of scientific portfólio, lesson, target log book, dossier, article and too much work), enriching the discovered activity proposal and sowing. The approach is in systemize a variation for the effective didactic transposition of the scientific knowledge to the pertaining to school knowledge. The elements articuladores pointed for the Curricular Lines of direction of the Physical Education with respect to high school of the State of the Paraná (Julho/2006) - the desportivização; the media; the body; the health; the leisure; tactics and technique; the diversity - they are boarded as vertebrador axle of present the proposal.